Treatment of keloids with pulsed dye laser in a pediatric population - Riccardo Cavalli; Nicola Adriano Monzani; Italo Francesco Aromolo (PAGEPress Publications, 2024)
Several studies confirmed the role of Pulsed Dye Laser (PDL) in successfully treating keloids. To our knowledge, this is the first study conducted entirely in children (<14 years old). Case notes and photographic records of 16 pediatric patients with keloids treated with PDL at our centre between 2012 and 2019 were reviewed. The red tone of the lesion before the first treatment, number of sessions, clinical improvement, and the evaluation of the satisfaction of patients have been reported. An excellent clearance has been achieved in 7 out of 16 (43.8%) cases, a good-moderate clearance in 7 patients (43.8%), and a slight clearance in 2 patients (12.4%). No patients detected absent or low results. A total of 13 out of 16 patients (81.2%) were satisfied. Lesions of higher red-tone grades were able to take advantage of multiple treatment sessions. PDL is an effective treatment of keloids in the pediatric population, characterized by a good safety profile and high satisfaction. We observed good results treating the active remodeling lesions with a higher red tone. These data have to be confirmed with further studies in a larger set of pediatric patients.